A Study on The Marriage Phenomenolgy of Commuter Marriage Spouse - Wismanto, Bagus; Nastiti, B’tari Sekar (Universitas Muhammadiyah Metro, 2017)
In general, the marriage is lived by a spouse who lives together and cooperates with each other to shape the family. Recently, many couples do not live together, but in a distant city, and are called a long-distance marriage or a commuter marriage. From many reasons that create the long distance marriage, one of which is the job. The aim of this study is to find out the condition of the marriage life in commuter marriage and the dynamics on perceived marital satisfaction. This research method uses the qualitative method. Subjects in this study are 3 pairs of husband and wife practicing commuter marriage, which has a minimum marriage age of 5 years and has at least one child. The research result has shown that wives tend to experience dissatisfaction in the marriage, while the husbands feel quite happy in the marriage.